Patina enrichment with SnO2 and its effect on soluble Cu cation release and passivity of high-purity Cu-Sn bronze in artificial perspiration. (1st September 2018) - Hutchison, M.J.; Scully, J.R.
Abstract: The antimicrobial function of Cu surfaces can be linked to soluble Cu release from corrosion. However, direct replacement of high-touch surfaces with Cu-based alloys is limited by knowledge gaps regarding how alloying directly relates to corrosion. A systematic approach to determine the role of Sn as a solute element and the minimum alloy content for passivation has been lacking. High-purity arc-melted binary alloys of Cu-Sn with specific additions of 0.1, 1, 5, and 10 wt% Sn were compared to pure Cu and Sn. The role and amount of Sn in corrosion products (patina) formed on the alloy surface as a function of alloying was interrogated in artificial perspiration. The fate and identity of the solute (Sn) and solvent (Cu) elements following corrosion, as soluble ions or insoluble corrosion products, was investigated. Alloy patinas became increasingly enriched in Sn corrosion products identified as SnO2 with increasing Sn content in the alloy. The critical alloy content for complete SnO2 layer coverage were theoretically quantified through a model based on interfacial surface energy. The predicted minimum solute content for a complete conformal inner layer of SnO2 was 1 wt% Sn whereas experimentally complete coverage was achieved only at 10 wt% Sn. Differences between theory and experiment are discussed.